PENGARUH INFLASI DAN NILAI TUKAR RUPIAH TERHADAP HARGA INDEKS SAHAM SYARIAH INDONESIA PERIODE TAHUN 2019-2021 - R, M. Apriliansyah.; Kurniawan, M. Agus; Firdaus, Adam (Ekonomika, 2024)
This research discusses the influence of inflation and the Rupiah exchange rate on the price of the Indonesian Sharia Index for the 2019-2021 period. This type of research is quantitative, the data used in this research is cross section secondary data published by Bank Indonesia (BI). The analytical method used is Multiple Linear Regression Analysis. The research results show that inflation and the Rupiah exchange rate have a significant effect on the Indonesian Sharia Stock Index Price for the 2019-2021 period. The coefficient of determination value obtained is an R square value of 0.502 or equal to 50.2%. This shows that the contribution of the influence of inflation and the Rupiah exchange rate on the Indonesian Sharia Stock Index Price for the 2019-2021 period is 50.2%. Meanwhile, the remaining 49.8% is influenced by other variables not included in the research, such as interest rates, levels of imports of goods, political and legal conditions and overall stock market conditions which influence the price of the Indonesian sharia stock index.